2009
DOI: 10.1111/j.1471-0528.2008.02056.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus interrupted sutures for repair of episiotomy or second‐degree perineal tears: a randomised controlled trial

Abstract: Objective To evaluate the repair techniques of continuous and interrupted methods for episiotomy or perineal tears.Design A randomised controlled trial.Setting The Hospital Universitario Principe de Asturias, a state hospital belonging to the community of Madrid.Sample Four hundred forty-five women who had undergone vaginal deliveries with episiotomies or second-grade tearing of the perineum between September 2005 and July 2007.Methods One group was repaired with continuous, nonlocking sutures involving the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 17 publications
(21 reference statements)
3
35
1
5
Order By: Relevance
“…1 17 As the present included studies did not analyse the results based on different comorbidities, age, or skin type, we do not know whether patients with difference skin types might present with differing outcomes-for example, Afro-Caribbean patients are more susceptible to hypertrophic and keloid scarring. 22 Previous studies have examined the clinical outcomes of skin closure with continuous or subcuticular interrupted suture techniques for repair of episiotomy or second degree perineal tears [23][24][25] and vascular surgery. 26 27 Most orthopaedic studies used interrupted subcuticular suture techniques for wound closure, while only two studies adopted a continuous suture technique.…”
Section: Discussionmentioning
confidence: 99%
“…1 17 As the present included studies did not analyse the results based on different comorbidities, age, or skin type, we do not know whether patients with difference skin types might present with differing outcomes-for example, Afro-Caribbean patients are more susceptible to hypertrophic and keloid scarring. 22 Previous studies have examined the clinical outcomes of skin closure with continuous or subcuticular interrupted suture techniques for repair of episiotomy or second degree perineal tears [23][24][25] and vascular surgery. 26 27 Most orthopaedic studies used interrupted subcuticular suture techniques for wound closure, while only two studies adopted a continuous suture technique.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that the surgical time may be reduced by ≤30 min for each stapled anastomosis (27) and the continuous suture may also contribute to the reduction in surgical time without increasing the complication rate in various types of surgery (28). There was no significant difference in surgical time between the new manual and traditional suture technique in this study.…”
Section: Discussionmentioning
confidence: 48%
“…Continuous suture contributes to reduced surgical time, and does not increase complication in episiotomy (31). Staple anastomosis reduces surgical time by ≤30 min due to cutting and suturing tissues only once (32); however, to acquire a safe anastomosis, a sharp blade and a sufficient amount of tissue cutting is required, which may lead to surgical issues and prolong surgery time.…”
Section: Discussionmentioning
confidence: 99%